(untitled) (Bangladesh Journal of Child Health, 2022)
Alternating hemiplegia of childhood (AHC) is a rare neurological disorder manifested by transient repeated episodes of alternating hemiplegia associated with other neurological events. Though the exact etiology was largely unknown, recently the pathogenic mutation in the ATP1A3 gene encoding for the alpha3 catalytic subunit of Na+/ K+ATPase was found to be the primary cause of AHC. We present the case of 8.5 year old girl with AHC who had a heterozygous de-novo p.Leu839Pro (c.2516T>C) pathogenic mutation of ATP1A3 gene on chromosome 19q13. BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 175-177